Effect of Fruit Pruning and Potassium Application on Growth and Production of Strawberry (Fragaria chiloensis). - Efbertias Sitorus; Lince Romauli Panataria; Meylin Kristina Saragih; R. Lubis (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of fruit pruning and application of Potassium on the growth and production of strawberry plants (Fragaria chiolensis). This study used a randomized block design (RBD) with 2 factors. The first factor was fruit pruning consisting of 4 levels: P0 = No pruning, P1 = 1 pruning, P2 = 2 pruning, P3 = 3 pruning. The second factor is Potassium fertilizer consisting of 4 levels: K0 = 0 g/plant, K1 = 2 g/plant, K2 = 4 g/plant, K3 = 6 g/plant. The observed variables were plant height (cm), flowering age (days), Fruit Weight (g), Fruit Volume (cm3), Sugar Content (%), Plant Wet Weight (g), and Plant Dry Weight (g). The results showed that pruning three fruits/plant increased plant height, fruit weight, fruit volume, sugar content, fresh weight and dry weight. Applying potassium fertilizer up to a dose of 6 g/plant can increase plant height, flowering time, fruit weight, fruit volume, sugar content, and wet and dry weight. Meanwhile, the interaction between fruit pruning and potassium application had no significant effect on all observed parameters.